1998
DOI: 10.1159/000045053
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Uremic Iron Deficiency Anemia in Hemodialyzed Patients: A Prospective Study

Abstract: This prospective study was designed to evaluate the eventual correction of anemia and iron status in 39 iron-deficient uremics starting hemodialysis. Nine patients (control group) had no iron supplementation, 10 had oral ferrous iron, and 20 were treated with intravenous iron gluconate. Follow-up periods were 12 months for the control group and 26 months for patients treated with oral or intravenous iron. No patient was treated with erythropoietin. At zero time, all patients were anemic (Hb <78 g/l) and showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
74
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 35 publications
1
74
0
3
Order By: Relevance
“…In contrast, among patients receiving hemodialysis, three randomized clinical trials found no demonstrable efficacy for oral iron. [19][20][21] IV iron has better defined efficacy, but its use in NDD-CKD is limited by documented and perceived risks and the inconvenience of administering IV iron in the outpatient setting.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, among patients receiving hemodialysis, three randomized clinical trials found no demonstrable efficacy for oral iron. [19][20][21] IV iron has better defined efficacy, but its use in NDD-CKD is limited by documented and perceived risks and the inconvenience of administering IV iron in the outpatient setting.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23] Historically, oral supplementation with ferrous salts in the absence of food failed to meet the erythropoietic demands of absolute and functional iron deficiencies in patients with ESRD, largely because of GI intolerance that limited dosing to approximately 200 mg elemental iron per day. [23][24][25] This inefficiency of oral iron supplementation led to the widespread use of iv iron in patients on dialysis, with the Dialysis Outcomes and Practice Patterns Study Practice Monitor reporting over 70% of patients on dialysis receiving iv iron at any given time in 2011. 26 Ferric citrate delivered much larger doses of elemental iron with food (up to 2520 mg/d) compared with previous oral preparations, and hence, it reduced or eliminated the need for iv iron.…”
Section: Discussionmentioning
confidence: 99%
“…In ESAtreated patients, therefore, failure of an inexpensive adjuvant may increase the effective cost of anemia management. Although RCT have shown intravenous iron to be superior to oral iron in ESA-treated HD patients (12)(13)(14) and patients with CKD (15), RCT in PD patients are currently lacking. Our study provides needed information to guide the design, size, and duration of such a comparative trial.…”
Section: Discussionmentioning
confidence: 99%